WAYS TO INCREASE INTER-INSTITUTIONAL COMPETITION IN SOCIAL MANAGEMENT ACTIVISM OF NEIGHBORHOOD INSTITUTIONS - Tashtemirova Zilala Madaminovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
this scientific article also provides information on the work currently being carried out and their nickname.